Factors Affecting Job Satisfaction of Ethiopian Revenue and Customs Authority Employees at Head Office - Mebratu, Mahtem (African Journal of Leadership and Development, 2019)
Job satisfaction is vital to maintain and retain employees within the organization and reduce the expense of hiring new employees; Even with the authority hiring new graduates from different universities, turnover is increasing from year to year. The challenge is indeed severe, instigated by poor motivation and resulting in job dissatisfaction (ERCA, 2016). The research design was descriptive, and the research was conducted by using both primary and secondary data. The sampling technique used was stratified sampling. Simple random sampling method was employed after the employees were stratified by educational level. The sample size was 271 selected from the total employee population. The study found that employees of ERCA are not satisfied with their jobs due to the absence of growth and development opportunities, job insecurity, poor working conditions, and lack of recognition programs. Moreover, the promotional policies are not known by the employees, and staff members are not promoted on merit or based on their experience and/or performance. Finally, the study recommends that compensation and incentive packages be developed and implemented properly. Well organized career structure opportunities should be put in place. Supervisors should empower officers and even require them to make decisions independently. Managers/Supervisors/Team Leaders should evaluate based on performance and develop recognition programs to encourage best performance.